Differential Impact of Blood Pressure Control Targets on Epicardial Coronary Flow After Transcatheter Aortic Valve Replacement - Brennan J. Vogl, BS; Alejandra Chavez-Ponce, MD; Adam Wentworth, MS; Eric Erie, AAS; Pradeep Yadav, MD; Vinod H. Thourani, MD; Lakshmi Prasad Dasi, PhD; Brian Lindman, MD, MSc; Mohamad Alkhouli, MD; Hoda Hatoum, PhD (Structural Heart, 2024)
Background: The cause for the association between increased cardiovascular mortality rates and lower blood pressure (BP) after aortic valve replacement (AVR) is unclear. This study aims to assess how the epicardial coronary flow (ECF) after AVR varies as BP levels are changed in the presence of a right coronary lesion. Methods: The hemodynamics of a 3D printed aortic root model with a SAPIEN 3 26 deployed were evaluated in an in vitro left heart simulator under a range of varying systolic blood pressure (SBP) and diastolic blood pressure (DBP). ECF and the flow ratio index were calculated. Flow index value <0.8 was considered a threshold for ischemia. Results: As SBP decreased, the average ECF decreased below the physiological coronary minimum at 120 mmHg. As DBP decreased, the average ECF was still maintained above the physiological minimum. The flow ratio index was >0.9 for SBP ≥130 mmHg. However, at an SBP of 120 mmHg, the flow ratio was 0.63 (p ≤ 0.0055). With decreasing DBP, no BP condition yielded a flow ratio index that was less than 0.91. Conclusions: Reducing BP to the current recommended levels assigned for the general population after AVR in the presence of coronary artery disease may require reconsideration of levels and treatment priority. Additional studies are needed to fully understand the changes in ECF dynamics after AVR in the presence and absence of coronary artery disease.